2006
DOI: 10.1111/j.1471-4159.2006.03727.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte‐colony stimulating factor is neuroprotective in a model of Parkinson's disease

Abstract: We have recently shown that the hematopoietic GranulocyteColony Stimulating Factor (G-CSF) is neuroprotective in rodent stroke models, and that this action appears to be mediated via a neuronal G-CSF receptor. Here, we report that the G-CSF receptor is expressed in rodent dopaminergic substantia nigra neurons, suggesting that G-CSF might be neuroprotective for dopaminergic neurons and a candidate molecule for the treatment of Parkinson's disease. Thus, we investigated protective effects of G-CSF in 1-methyl-4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 70 publications
(69 reference statements)
2
70
2
1
Order By: Relevance
“…Numerous reports have described the efficacy of G-CSF in animal models of different neurological diseases including stroke (Schabitz et al, 2003;Schneider et al, 2005;KomineKobayashi et al, 2006;Solaroglu et al, 2006;Minnerup et al, 2008), Parkinson's disease (Cao et al, 2006;Meuer et al, 2006), and Alzheimer's disease (Tsai et al, 2007). These studies confirm G-CSF as a neurotrophic factor, and ascertained its role in neuroprotection and neuroregeneration relevant to the most prominent neurodegenerative diseases.…”
Section: Introductionsupporting
confidence: 51%
“…Numerous reports have described the efficacy of G-CSF in animal models of different neurological diseases including stroke (Schabitz et al, 2003;Schneider et al, 2005;KomineKobayashi et al, 2006;Solaroglu et al, 2006;Minnerup et al, 2008), Parkinson's disease (Cao et al, 2006;Meuer et al, 2006), and Alzheimer's disease (Tsai et al, 2007). These studies confirm G-CSF as a neurotrophic factor, and ascertained its role in neuroprotection and neuroregeneration relevant to the most prominent neurodegenerative diseases.…”
Section: Introductionsupporting
confidence: 51%
“…It has been suggested that a specific neuronal receptor may be responsible for the neuroprotective action of EPO that consists of a heterodimer of the EPO receptor and the GM-CSF b-receptor (Brines et al, 2004), suggesting a possible inherent connection of the neuroprotective properties of both proteins. Recently, we have uncovered the neuroprotective potential of G-CSF (Meuer et al, 2006;Schabitz et al, 2003;Schneider et al, 2005Schneider et al, , 2006Schabitz and Schneider, 2007). The parallels in expression, reactivity, and function of these two factors are surprising: Both react to injury by upregulation, have an antiapoptotic function on neurons, trigger an identical subset of intracellular signaling pathways, and are co-expressed with their receptors.…”
Section: Discussionmentioning
confidence: 99%
“…4 Induction of antiapoptotic cascades in vitro is immediate, with phosphorylation and activation of v-Akt murine thymoma viral oncogene homolog within 5 minutes after addition of G-CSF to the neurons. 4 Antiapoptotic effects of G-CSF were observed in a variety of different neuron types or neuronal cell lines, such as dopaminergic cells, 25 motoneurons, 26 and primary cortical and hippocampal neurons. 4,27 Mechanisms include induction of signal transducers and activators of transcription 3 signaling; phosphorylation of extracellular signal-regulated protein kinase-1, -2, and -5; and activation of Akt kinase, the last of which appears to be responsible for Ϸ70% of the efficacy of G-CSF in vitro, as previously demonstrated by inhibition experiments.…”
Section: G-csf 'Freezes' the Penumbramentioning
confidence: 99%